Kemampuan Pragmatik dalam Interaksi Sosial Anak Tunarungu Melalui Penggunaan Metode Komunikasi Total - Dimy Mullyana; Asri Wijiastuti (Jurnal Pendidikan Kebutuhan Khusus, 2019)
ABSTRACT This research aims to determine the pragmatic ability of the deaf child in the aspect of social interaction with the use of the total communicational supporting aspects (oral, aural and manual). One aspect of pragmatic ability to do two-way communication with interaction. This research in SLB-B Kab. Sidoarjo consisting of 8 research subjects and 5 informant. The research method used is a qualitative descriptive with the instrument of the data collector used i.e. observation, interviews and documentation. The results of the research obtained is the ability of deaf children in initiating, maintaining and ending communication politely in domination with oral (speech), manual (gesture, finger spelling, gesture, and expression) and the use of 1-3 words. Keywords: pragmatic;interaction social; total communication;